Potensi Komunitas Bakteri Simbion Cacing Tanah Vermiwash dalam Memproduksi Fitohormon IAA pada Jagung - Oktafian, Akhmad Rizal; Septia, Erfan Dani; Nursandi, Fatimah (Agrotechnology Research Journal, 2023)
Bacteria living in the digestive system of earthworms (Eudrilus eugeniae) can play a role in transforming organic compounds found in the organic matter digested by the worms into simple compounds, including compounds containing indole. During the fermentation process in vermiwash, bacteria will consume the organic matter in worm waste and produce IAA as a byproduct of metabolism. This research aims to analyse the potential symbiotic bacterial communities in vermiwash from earthworms (African Night Crawler) in producing the plant hormone IAA (Indole Acetic Acid). The research method involves collecting vermiwash from earthworms and analysing its symbiotic bacterial composition. Symbiotic bacterial isolates from vermiwash were tested for their ability to produce IAA through biochemical techniques, followed by bioinformatic analysis. The research results show that vermiwash contains a potential symbiotic bacterial community capable of producing IAA. Three isolates out of 10 types of symbiotic bacteria yielded positive results by showing a pink colour change after adding the Salkowski reagent. Therefore, these symbiotic bacteria can be utilized as a source of the plant hormone IAA, which can be used as organic fertilizer. Increased IAA production in vermiwash, can accelerate plant growth, enhance root formation, and optimize overall plant production. The application of a bacterial consortium can significantly influence the plant height, leaf area, and root length while having a non-significant impact on the stem diameter of corn.